2012
DOI: 10.1074/jbc.m111.326041
|View full text |Cite
|
Sign up to set email alerts
|

MiR-3120 Is a Mirror MicroRNA That Targets Heat Shock Cognate Protein 70 and Auxilin Messenger RNAs and Regulates Clathrin Vesicle Uncoating

Abstract: Background: “Mirrored” or complementary mammalian miRNAs have been predicted but none have yet been characterized.Results: miR-3120 and miR-214 are produced from the same intronic locus; miR-3120 regulates heat shock cognate protein 70 (Hsc70) and auxilin expression and vesicle uncoating.Conclusion: miR-3120 is a mirror miRNA regulating endocytic function.Significance: Mirror miRNAs are important mammalian gene regulatory units, and many more remain to be found and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…In addition to miR emergence, a new miR, miR3120, was revealed by high-throughput sequencing in human, rat, cow and in the Jamaican fruit bat 52 and the miR3120 gene overlaps miR214 with nearly complete overlap but on the opposite strand, and is thus categorized as a mirrormiR. 53,54 Expression of mirror-miRs has been demonstrated in Drosophila, 53 but to our knowledge, miR3120 is the only experimentally documented mirror-miR in vertebrates. 54 As one would expect from an intronic miR, miR3120 has been shown to be co-expressed with and to regulate important aspects of cellular function similar to its same-stranded host coding gene Dnm3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to miR emergence, a new miR, miR3120, was revealed by high-throughput sequencing in human, rat, cow and in the Jamaican fruit bat 52 and the miR3120 gene overlaps miR214 with nearly complete overlap but on the opposite strand, and is thus categorized as a mirrormiR. 53,54 Expression of mirror-miRs has been demonstrated in Drosophila, 53 but to our knowledge, miR3120 is the only experimentally documented mirror-miR in vertebrates. 54 As one would expect from an intronic miR, miR3120 has been shown to be co-expressed with and to regulate important aspects of cellular function similar to its same-stranded host coding gene Dnm3.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 Expression of mirror-miRs has been demonstrated in Drosophila, 53 but to our knowledge, miR3120 is the only experimentally documented mirror-miR in vertebrates. 54 As one would expect from an intronic miR, miR3120 has been shown to be co-expressed with and to regulate important aspects of cellular function similar to its same-stranded host coding gene Dnm3. 54 In teleost fish, five to six dynamin genes have already been annotated ( Table 1; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, miR-214 is known to target phosphatase and tensin homolog (PTEN), which interacts with DNM and regulates receptor recycling (Yang et al, 2008). More interesting, the mirror miRNA miR-3120, which is fully the complement of miR-214 in the DNM3 intron, is co-expressed with its host gene mRNA and regulates uncoating of clathrin-coated vesicles by targeting Hsc70 and auxilin (Scott et al, 2012). These studies are in agreement with our hypothesis that DNM intronic miRNAs regulate important aspects of cellular functions that are similar to those regulated by its host gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depletion of miR-320 enhances levels of its downstream target HSPB6/ HSP20 to protect cardiomyocytes from I/R-induced death (Ren et al 2009). It has also been shown that miR-3120 plays a role in regulating constitutive levels of HSPA8/Hsc70 in neuronal cells by targeting multiple conserved sites within its 3′UTR (Scott et al 2012). Because HSPA8/Hsc70 catalyzes the uncoating of clathrin-coated vesicles, miR-3120 overexpression prevents vesicle uncoating.…”
Section: Mirnas Target Heat Shock Protein Transcriptsmentioning
confidence: 99%